Los signos de puntuación: la coma y el punto - Avalos Valle, Jenny Cecilia (2019)
The purpose of this work is for the student to write texts correctly using the comma and period punctuation marks. So that your writing development overcomes the limitations of a person in training, so a learning session was raised are their respective pedagogical processes and annexes. In addition, the theoretical support of the subject is approached to give the solid bases from the cognitive approach with the different linguistic theorists, also it was developed in pedagogical support to know the minors of how the didactic and pedagogical knowledge is embodied in the processes of teaching-learning Therefore, this class session is framed by the principles of education that constantly become social and technological changes._x000D_ Finally, it is stated that without good academic training, the social system would not continue to develop vertiginously, so we must give value to the social, political, economic and cultural changes that we have had to experience, of course, promoting education and especially education for the development of relevant writing learning.